Scalable model of pediatric inguinal hernia surgery in remote Nepal: prospective study to change practice - KC, Archana; Dangal, Binod; NG, Jessica; Parker, Shabnam (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Inguinal hernia is the common surgical problem in children. Most of the inguinal hernia in children are congenital due to patent processes vaginalis. Due to inadequate numbers of surgeons in remote Nepal, most of the childhood hernia are referred or left untreated. The study evaluates the outcomes of pediatric hernia surgery performed by General Practitioners (GPs) after training GPs in remote setting by pediatric and general surgeons Method: It is a prospective study of pediatric hernia surgeries performed by general practitioners after targeted inguinal hernia surgery workshops and hands on training by group of general and pediatric surgeons at Charikot Hospital and Tsho-Rolpa General Hospital at Dolakha district of rural Nepal from 1st December 2019 to November 30th 2023 and a year of follow up for the age group of 3-18 years. Data was collected through Electronic Health Record (EHR) system and surgery register Result: During study period, 204 children underwent herniotomy, out of which 131 (65.2%) were boys while 73(35.8%) were girls. Among them, 151(74%) had unilateral inguinal hernia, 31(15.2%) had bilateral and remaining 22(10.8%) had unilateral hydrocele. Among 151 children, 98(65%) had right sided inguinal hernia. Among 204 cases, 9 (4.4%) had scrotal edema, 6(2.9%) had wound infection and 2(1%) had recurrence in 1-year post surgery follow up. Conclusion: This prospective study highlights the feasibility of implementing a scalable, community-based surgical model for pediatric inguinal hernia repair in remote areas of Nepal. GPs can be trained to perform inguinal herniotomy to improve surgery access in remote setting.